Buying and Selling Transactions Using Paid Member Cards From The Perspective of Islamic Economic Law - nadiatul saravina; Agustin Hanapi; Azka Amalia Jihad (Program Studi Hukum Ekonomi Syari'ah, 2026)
The development of modern trade has introduced various marketing innovations, one of which is the use of paid member cards that offer discounts, shopping points, and exclusive benefits. However, when the use of member cards requires a registration fee, questions arise regarding the clarity of benefits, compliance with the principles of Islamic economic law, and consumer rights protection. This study aims to analyze consumer rights in the use of paid member cards and to evaluate the practice from the perspective of Islamic economic law. The research employed a qualitative descriptive-analytical method with a juridical-empirical approach, through interviews and literature review. The results indicate that the practice of paid member cards has the potential to create uncertainty of benefits and an imbalance between costs and gains, especially when information is not transparent. From the perspective of Islamic economic law, this practice is permissible provided that benefits are clearly defined, free from gharar (uncertainty) and maysir (speculation), and the fees charged are limited to administrative costs. In practice, at Kotty Kosmetik Banda Aceh, some consumers reported a lack of certainty regarding products eligible for discounts, limited information on items that can be redeemed with points, and relatively high registration fees. Therefore, the implementation of information transparency and cost limitation principles is essential to ensure justice, protect consumer rights, and maintain compliance with Islamic economic law.